Computational and Experimental Mechanics of Advanced Materials - Silberschmidt, Vadim V.; SpringerLink (Online service) (Vienna : Springer Vienna, 2010)
Advanced materials play a crucial role in modern engineering applications where they are often exposed to complex loading and environmental conditions. In many cases, new approaches are needed to characterise these materials and to model their behaviour. Such approaches should be calibrated and validated by specific experimental techniques, quantifying both microstructural features and respective mechanisms at various length scales. The book provides an overview of modern modelling tools and experimental methods that can be employed to analyse and estimate properties and performance of advanced materials. A special feature of the book is the analysis of case studies used to demonstrate the strategies of solving the real-life problems, in which the microstructure of materials directly affects their response to loading and/or environmental conditions. The reader will benefit from a detailed analysis of various methods as well as their implementation for dealing with various advanced materials.
Experimental Analysis of Mechanical Behaviour of Advanced Materials -- Localization and dynamic defects in lattice structures -- A 3-D brick Cosserat Point Element (CPE) for nonlinear elasticity -- Multiscale Approaches: From the Nanomechanics to the Micromechanics -- Analytical and Numerical Methods for Modeling the Thermomechanical and Thermophysical Behavior of Microstructured Materials -- Effect of Microstructure: Multi-scale Modelling.
Keywords: Engineering; Mechanics; Engineering mathematics; Materials; Engineering; Appl.Mathematics/Computational Methods of Engineering; Continuum Mechanics and Mechanics of Materials; Mechanics